Salvage LATTICE radiotherapy for a growing tumour despite conventional radio chemotherapy treatment of lung cancer. (March 2023) - Kinj, Rémy; Casutt, Alessio; Nguyen-Ngoc, Tu; Mampuya, Ange; Schiappacasse, Luis; Bourhis, Jean; Huck, Constance; Patin, David; Marguet, Maud; Zeverino, Michele; Moeckli, Raphaël; Gonzalez, Michel; et al.
Highlights: LATTICE radiotherapy (LRT) is a form of spatially fractionated radiotherapy inspired from GRID radiotherapy. LRT is usually used as a boost or in a palliative intent. LRT permits a dose escalation into the tumor while preserving surrounding organs at risk. LRT is presented in this report as a salvage boost treatment. Abstract: A 40-year-old patient with cT4cN1M0 squamous cell lung cancer of the upper right lobe received preoperative induction chemotherapy. Systemic induction treatment failed to reverse tumour growth with the addition of conventional radiotherapy (RT). A salvage lattice RT boost of 12 Gy was administered immediately to increase the dose to the tumour. Conventional RT was resumed at the planned dose of 60 Gy. The tumour shrank rapidly, and the patient was surged. The postoperative pathology remained ypT0ypN0 status.